A Method for Capturing Context in the Assessment of Leaders: The "Too Little/Too Much" Rating Scale. Issue 4 (December 2018) - Vergauwe, Jasmine; Kaiser, Robert B.; Wille, Bart; De Fruyt, Filip; Hofmans, Joeri
Abstract : In their focal article, Reynolds, McCauley, Tsacoumis, and the Jeanneret Symposium Participants (2018 ) stress the importance of context in leadership assessment. For instance, they argue that senior executives work in a different context compared to lower-level managers and that this should be taken into account. A simple example is that the competency of strategic thinking is critical for executive performance but much less so, if at all, for front-line supervisors. The claim that context matters in leadership and in the assessment of leaders is easy to grasp but difficult to apply in practice.